Software engineering a practitioner's approach - Pressman, Roger S.; Maxim, Bruce R. (McGraw-Hill Education, 2015)
A guide to software engineering. It focuses on widely used software engineering methods and will de-emphasize or completely eliminate discussion of secondary methods, tools and techniques.